Estimating the Clinical and Economic Impact of Maintaining use of 13-valent Pneumococcal Conjugate Vaccine (PCV13) in Mexico. (4th October 2017) - Wasserman, Matt; Wilson, Michele; McDade, Cheryl; Grajales, Ana Gabriela; Palacios, Maria Gabriela; Baez- Revueltas, Fabiola Berenice; Farkouh, Raymond
Abstract: Background: PCV13 replaced 7-valent pneumococcal conjugate vaccine in the routine infant immunization schedule in Mexico since 2011. The use of PCV13 has reduced pneumococcal disease incidence for vaccine serotypes, particularly 19A, which emerged following PCV7 use. The 10-valent vaccine (PCV10) contains the same serotypes as PCV13 with the exception of serotypes 3, 19A and 6A but also has different conjugated proteins for the common serotypes. This study evaluated the potential health and economic implications of switching from PCV13 to PCV10 in Mexico. Methods: A decision-analytic model was developed to estimate public health and economic impact of maintaining PCV13 compared with switching to PCV10 in Mexico. Disease incidence at time of potential switch for invasive pneumococcal disease (IPD), pneumonia (PNE) and acute otitis media (AOM) was obtained from Dirección General de Epidemiología and the published literature. Historical data was used to estimate IPD trends under different infant vaccine pressures and the model forecasted disease across the population. For each vaccination program, health outcomes and associated health-care costs were estimated. Costs, utility weights, and risk of disease-specific complications were derived from published sources. Results: In the base case, continued use of PCV13 would result in significantly fewer cases of pneumococcal disease than switching to PCV10 in Mexico (See Table 1). Despite a higher vaccine cost, PCV13 was cost-saving compared with PCV10 in the base case and across a number of scenarios evaluated. Conclusion: Continued use of PCV13 in Mexico is predicted to provide greater public health benefit compared with switching to PCV10 not only economically but also socially. It is important that policy makers consider potential implications of disease re-emergence of non-covered serotypes when considering modifications to vaccination strategies. Disclosures: M. Wasserman, Pfizer: Employee, Salary; M. Wilson, Pfizer: Consultant, Consulting fee; C. McDade, Pfizer: Consultant, Consulting fee; A. G. Grajales, Pfizer: Employee, Salary; M. G. Palacios, Pfizer: Employee, Salary; F. B. Baez- Revueltas, Pfizer: Employee, Salary; R. Farkouh, Pfizer: Employee, Salary.